Ictal syncope or isolated syncope? A case report highlighting the overlap. Issue 11 (5th October 2021) - Fanous, Yehia; Astrada, Miguel A; Mirsattari, Seyed; Khan, Habib R
Abstract: Background: Ictal bradyarrhythmia is a rare condition defined by temporal lobe epilepsy resulting in bradycardia or asystole and can result in syncope. This needs to be differentiated from isolated syncope in patients with seizure disorder, as treatment strategies differ. Case summary: A 50-year-old female with well-controlled temporal epilepsy and a 20-year seizure-free period presented to her neurologist with abrupt onset of sudden drop attacks thought to be ictal events with potential underlying ictal bradyarrhythmia and was initially treated with escalation of anticonvulsant therapy. However, her workup was consistent with a diagnosis of cardiac syncope. She subsequently underwent successful insertion of a pacemaker, with no recurrence of her presenting episodes at a 13-month follow-up. Discussion: Ictal syncope and isolated syncope may share a common terminal pathway and may have similar presenting symptoms. In patients with known seizure disorder, loss of consciousness may be attributable to epileptic events, ictal syncope, or isolated syncope—which can be difficult to differentiate. This case highlights the ambiguous nature of such episodes and the importance of simultaneous electroencephalogram/electrocardiogram monitoring, as this can have implications on treatment.